Histological and histochemical characterization of the digestive tract of European catfish (Silurus glanis Linnaeus, 1758) - Koprucu, S.; Yaman, M. (C M B Assoc, 2016)
In this study was to examined the morphology, histology and histochemically the digestive tract of European catfish, Silurus glanis. Two-four age S. glanis obtained from Celik Lake (Golbasi-Adiyaman, Turkey). Six S. glanis, 59-71 cm length, 1.5-3.2 kg weight used for in the investigation. The body cavity was opened and samples of digestive tract (esophagus, stomach and intestine) were fixed in neutral buffered 10% formalin and embedded in paraffin. Dewaxed section (5-6 mu m) were deparaffinized and stained with haematoxylin and eosin (H&E), Crossman triple, periodic acid-shiff (PAS), alcian blue (AB, pH 1.0 and 2.5) and PAS+AB pH 2.5 tecnique for different structures. The histological and histochemical structures of all specimens were viewed under a light microscope and microphotograph. The histological structure consists of four layer: tunica mucosa, submucosa, tunica muscularis and tunica serosa. The short esophagus of S. glanis have numerous deep longitudinal folds, squamous epithelium with numerous mucous cells which react positively to PAS and AB stains. The muscularis mucosa was organized in longitudinal and circular layers of striated muscular fibers. The stomach is sac-like shaped and its mucosa was formed by simple columnar epithelium with folds. Histologically, the stomach shows three different region: cardia, fundus and pylorus region. The surface epithelium of stomach reacted positively to PAS and AB (pH 1.0 and 2.5). The mucosal surface of intestine of S. glanis has numerous folds lined by simple tall columnar cells. There were large number goblet cells in the intestine. The goblet cells reacted to PAS and AB (pH 1.0 and 2.5).
Keywords: Silurus glanis; histology; histochemical; digestive tract